Read-a-thon with SK Pulau Mansuk: creative minds and fun language learning through children's literature - Abas, Nadhratunnaim; Tengku Shariff, Tengku Intan Suzila (Universiti Teknologi MARA, 2009)
Reading literary works can help produce creative minds through fun language learning. In the Read-a-Thon programme, organised by the Academy of Language Studies UiTM Pahang, held in July 2007, its modules involved the reading of a short story and a poem from children's literature. The activities involved; Musical Story, and outdoor, Poem Explorace, were held indoor. Fifty Year Four, Five and Six students of SK Pulau Mansuk participated in this annual community service event. For the purpose of evaluation, all the fifty students were asked to complete a set of questionnaire at the end of the programme. Though reading literary works might be new to these students, their responses were positively overwhelming.